Representasi Kekerasan Pada Remaja Di Amerika Serikat (Analisis Semiotika Roland Barthes Pada Film Scream Vi ) - Puspita, Rani Widya; Aladdin, Yuri Alfrin; Samatan, Nuriyati (CV. Green Publisher Indonesia, 2025)
Movies as mass media not only serve as entertainment, but also represent social phenomena. This study analyzes the meaning of violence in the film Scream VI using Roland Barthes' semiotic method with a qualitative approach and representation theory. The results show that violence in Scream VI is represented through three main aspects: physical violence in brutal murder as a form of revenge, psychological violence due to repeated trauma and fear, and myths that build the narrative that violence is a form of self-defense and a way to get justice. The film also shows how emotionally wounded individuals are caught in a cycle of revenge. This research contributes to the study of communication and media by providing insights into the representation of violence in horror films as well as its impact on adolescents. These findings can serve as a reference for academics, film critics, and policymakers in understanding the influence of media on public perception.